Transcriptome analysis identifies key regulatory genes and temporal expression dynamics during embryonic development in the Japanese eel (Anguilla japonica) - Zhaowei Zhong; Dingyuan Luo; Yizhen Lu; Zebin Chen; Ning Xi; Shengkai Shi; Jincan Chen; Yonghua Jiang (Molecular Genetics and Genomics, 2026)

Gene cloning and expression analysis based on primary culture of fin cells from Centropyge vrolikii - Dingyuan Luo; Ning Xi; Shengkai Shi; Yizhen Lu; Zebin Chen; Hongwei Liu; Jincan Chen; Hai Huang; Zhaowei Zhong; Yonghua Jiang (Journal of Fish Biology, 2026)
Skin coloration is a distinctive phenotype and an economically important trait in ornamental fish. Understanding its regulatory mechanisms is crucial for both aquaculture and selective breeding. In this study, we cloned and analysed the full‐length complementary DNA (cDNA) sequences of four key pigmentation‐related genes— mitf , mc1r , tyr and sox10 —in the black‐tailed angelfish ( Centropyge vrolikii ). We established the fin‐derived tissue cell line of C. vrolikii (CVFTCL) and confirmed its transfection efficiency using EGFP, achieving 40%–50% expression 24 h post‐transfection, providing an in vitro platform for subsequent gene function verification. Using the primary fin cell culture system, we conducted overexpression and RNA interference (RNAi) experiments to investigate the regulatory relationships among these genes. Overexpression of mitf upregulated mc1r but downregulated sox10 and tyr ; overexpression of mc1r enhanced mitf expression while inhibiting sox10 and tyr ; overexpression of tyr only increased tyrp1 expression and overexpression of sox10 upregulated both mc1r and mitf , without affecting tyr . RNAi‐mediated knockdown confirmed the efficiency of gene silencing and supported the regulatory relationships inferred from overexpression experiments. Collectively, these findings indicate that mitf , mc1r , tyr and sox10 may interact to coregulate melanocyte development and melanin synthesis, thereby influencing skin coloration in C. vrolikii . This study provides a mechanistic framework for pigmentation regulation and a foundation for colour improvement and selective breeding in this species.

Overexpression of OsFH2 enhances cadmium tolerance and reduces grain cadmium accumulation in rice through synergistic root sequestration and antioxidant defense activation - Xinxin Xu; Shuchang Zhang; Qingxian Mo; Zebin Cai; Yao Cao; Ying Luo; Hongjie Chen; Fangbai Li; Jicai Yi (Journal of Hazardous Materials, 2026)

The evidence of H-O-C isotopes in response to earthquake and the precursor anomaly index: A case study of geothermal fluids in the Xianshuihe fault - Yi Yu; Hao Song; Jinlong Liang; Xuemin Liu; Zebin Luo; Jing Zhao; Zhipeng Li; Jinyong Xu (Geothermics, 2026)

Elucidating cooking-driven flavor dynamics of paddy field carp (Cyprinus carpio) using a combination of E-nose, E-tongue, GC-MS and GC-IMS - Chenying Fu; Jingying Weng; Fujing Luo; Mengxiang Liao; Lingzhan Xue; Zebin Guo (Food Chemistry, 2025)

Low-molecular-weight fucoidan prepared by ultrasonic/H2O2/VC degradation: Characterization, gut microbiota regulation, and anti-inflammatory effects - Huadan Zhang; Congcong Sun; Kailin Li; Xianliang Luo; Zebin Guo; Song Miao; Baodong Zheng (Food Bioscience, 2025)

Enhanced biodegradation of sulfamethazine in swine manure composting: Pathway elucidation, mechanism insights, and optimization of a novel Bacillus sp. strain - Xiaojun Lin; Jingtong Li; Chunyan Chen; Zifeng Luo; Hongxing Tu; Yuwan Pang; Xiujuan Wang; Qianyi Cai; Zebin Wei; Jianfeng Huang; Jingwen Zeng; Jinrong Qiu (International Biodeterioration & Biodegradation, 2025)

Response surface methodology and Box-Behnken design optimization of Sulfaquinoxaline removal efficiency and degradation mechanisms by Bacillus sp. strain DLY-11 - Chunyan Chen; Zifeng Luo; Hongxing Tu; Xiaojun Lin; Yuwan Pang; Jianfeng Huang; Jun Zhang; Xiujuan Wang; Qianyi Cai; Zebin Wei; Jingwen Zeng; Jinrong Qiu (Journal of Hazardous Materials, 2025)

Geothermal springs with high δ13CCO2-DIC along the Xianshuihe fault, Western Sichuan, China: A geochemical signature of enhanced deep tectonic activity - Jinlong Liang; Yi Yu; Zeming Shi; Zhipeng Li; Yi Huang; Hao Song; Jinyong Xu; Xinyu Wang; Xiaocheng Zhou; Luyu Huang; Zebin Luo; Jue Tong; et al. (Journal of Hydrology, 2023)

A 1-aminocyclopropane-1-carboxylate deaminase MrACCD from Metarhizium robertsii is associated with plant growth promotion for Metarhizium spp - Xinggang Liao; Qian Luo; Chao Wu; Dan Zhou; Jianfeng Li; Zebin Meng (Journal of Invertebrate Pathology, 2023)

Earthquakes evoked by lower crustal flow: Evidence from hot spring geochemistry in Lijiang-Xiaojinhe fault - Zebin Luo; Xiaocheng Zhou; Miao He; Jinlong Liang; Jingchao Li; Jinyuan Dong; Jiao Tian; Yucong Yan; Ying Li; Fengli Liu; Shupei Ouyang; Kaiyi Liu; et al. (Journal of Hydrology, 2023)

Yangshan A-Type Granites in the Lower Yangtze River Belt Formed by Ridge Subduction: Radiogenic Ca and Nd Isotopic Constraints - Jianghao Bai; Mingxing Ling; Xiaoyong Yang; Fang Liu; Huangling Gu; Zebin Luo; Xiaoyan Jiang; Zhaofeng Zhang (Journal of Earth Science, 2022)

Spatiotemporal pattern analysis of potential light seine fishing areas in the East China sea using VIIRS day/night band imagery - Lingwei Luo; Mengjun Kang; Jinhui Guo; Ying Zhuang; Zebin Liu; Yameng Wang; Liping Zou (International Journal of Remote Sensing, 2019)